Nekatere družbenogeografske posebnosti Haitija - Senegačnik, Jurij (Geografski obzornik, 2001)
Some of human geographical features of Haiti are presented. A special emphasisis laid on poverty, racial, linguistic and religious structure of the population. Also a short history of Haiti is briefly presented.
Keywords: družbene razmere; Haiti; potopisi; prebivalstvo; regionalna geografija; Srednja Amerika